(3UhQI GdMGOj YTQ ef SHJeHQ aj GdSjfeG GdeUQjI hGdCeQjcjI (B: s (3OQGSI JMdjdjI ebGQfI (B/ s - (3eGai eGgQ Cejf YHOGdedc s; (3fGOjI HOQGdOjf CHhZGRj (B: s ((3GdbGgQI (B: s (3eG(B{u(3FB6C(B}{u(3FBFD(B} (3eGgQCejf YHOGdedc (B: s, 2016)
(3JfGbT gPg GdQSGdI CgejI GdSjfeG cCMO Cge COhGJ GdbhI GdfGYeI ai GdYdGbGJ GdOhdjI(B. (3JJfGhd GdOQGSI Pdc ef NdGd YOI eOGNd HMKjI (B: (3Yde GdfaS GdSjGSi(B: (3Yde faS GdSjfeG(B: (3Yde ELJeGY GdSjfeG hGdJGQjNGfjI GdLOjOI dJKHJ eOi CgejI GdSjfeG ai GdJCKjQ Ydi Jchjf GdUhQ hHGdJGdi Ydi GdhYi hGdeTGYQ hGdSdhc dGSjeG ajeG jJYdb HbVGjG GdSjGSI GdNGQLjI hGdUhQ GdeJHGOdI Hjf TYHjf hHdOjf(B. (3dPdc bGeJ GdQSGdI HOQGSI JbOje CMOGK GdMGOi YTQ ef SHJeHQ hJOGYjGJgG ai GdSjfeG GdCeQjcjI hGdSjfeG GdeUQjI ai GdaJQI ef (B2001-2014 (3NdUJ GdQSGdI Edi GdJCcjO Ydi CgejI JaYjd OhQ GdSjfeG GdeUQjI cCOGI ddbhI GdfGYeI ef NdGd YOI JhUjGJ dUGfY GdbQGQ hddYGedjf HGdSjfeG hddLGeYGJ GdeUQjI dCf GdESJKeGQ ai GdSjfeG ESJKeGQ ai GdCef Gdbhei ceG ChVMJ GdQSGdI s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdEbJUGO hGdYdhe GdSjGSjI (B- (3bSe GdYdhe GdSjGSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdKbGaI GdSjGSjI s; (3GdUhQI GdbhejI GdPgfjI s; (3GdUhQI GdfeWjIs